A method to construct cDNA library of the entomopathogenic fungus, Metarhizium anisopliae, in the hemolymph of the infected locust - Zhang, C.; Cao, Y.; Wang, Z.; Yin, Y.; Peng, G.; Xia, Y.
A method was developed to construct cDNA library of pathogenic fungus in the blood of the infected insect for cloning the fungal genes expressed in the host. This method is designed to take advantage of the obvious difference between the cell structures and components of the pathogen cells and that of the host cells. The host blood cells only have cell membrane, which can be disrupted by using SDS/proteinase K (PK). The fungal cells grown in the animal blood have cell wall, which can protect the fungal cell from the disruption of SDS/proteinase K (PK). By this method, the blood cells were disrupted by SDS/ proteinase K (PK)and then the released animal RNA and DNA were digested completely with RNase and DNase. Therefore, the fungi grown in the blood were harvested without any contamination of host RNA and DNA. The pure fungi harvested from the infected blood can be used for mRNA extraction and cDNA library construction. The purity of the fungal mRNA was confirmed by PCR and RT-PCR with specific primer pairs for the host and specific primer pairs for the fungus, respectively, and the clones of cDNA library constructed by using the fungal mRNA was also analyzed. The results showed that there was no detectable contaminated insect DNA or RNA existing in the fungal mRNA. Randomly selected cDNA clones from cDNA library were sequenced and analyzed against GenBank using Blastx; no selected sequences had significant similarity with insects' genes in comparison with the data of GenBank. The results further confirmed that the method to purify the pathogenic fungus from the host animal is reliable and the mRNA extracted from the fungus is eligible for cDNA library construction, and other molecular analysis including RT-PCR. This method may be applied to other pathogenic fungi and their host animals.
Keywords: PATHOGENIC FUNGUS; INSECT; MRNA EXTRACTION; CDNA LIBRARY